Characteristic Features of the Past Form of the Spisz Dialect Verb ‘to be’ Based on Corpus Data - Grochola-Szczepanek, Helena (Jezikoslovni zapiski, 2019)
This article discusses the past form of the verb ‘to be’ in the Spisz dialect. The material is derived from the Spisz Dialect Corpus. Verb inflection in the dialect differs from standard Polish. Archaic forms such as byłech, jech był, and my byli are still used in the dialect. The number of occurrences of all the forms in the corpus is provided. Selected examples are presented in a broader context along with metadata. The author also presents the possibilities of using the electronic corpus for morphological and sociolinguistic research.